ANALISIS METODE PENETAPAN HARGA TERHADAP VOLUME EKSPOR RUMPUT LAUT PADA PT. CAHAYA CEMERLANG MAKASSAR - Hj. Nuraini Rasyid (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to determine the level of export sales of seaweed on the PT . Shining light Makassar last 3 years. to determine the contribution of exports to the level keutungan at PT . Shining light Makassar . The results showed that the market price strategy ( Live and Let Live Policy ) and high prices ( Skimming Price) applied by the Shining Light has an average volume of exports of the same seaweed . While the strategy of Live and Let Live Policy and strategy Price Skimming can detarapkan in Light Shining but applied to the circumstances and conditions that enable and between the importer and exporter there are no losers